Interdependence between Monetary Policy and Stock Liquidity: A Panel VAR Approach. (November 2018) - Debata, Byomakesh; Mahakud, Jitendra
This article examines the relationship between monetary policy and individual stock liquidity in an order-driven emerging stock market like India. This study considers stocks listed in National Stock Exchange of India (NSE) and continuously traded from April 2002 to March 2015. Considering the multiple dimensions of liquidity, this study uses five different liquidity proxies to capture the various facets of liquidity such as trading activity, price impact and transaction cost. An array of macroeconomic and firm-specific control variables are used while analysing the liquidity and monetary policy relationship. Econometric methods like panel vector autoregressive (VAR)–Granger causality test, impulse response functions and variance decomposition analysis have been employed to carry out this analysis. The empirical findings suggest that monetary policy significantly Granger-causes stock liquidity, and the expansionary monetary policy characterised by low interest rate and higher money supply is positively associated with individual stock liquidity in India. The impact of monetary policy on liquidity of individual stocks is more prominent during financial crisis. The findings of the present study have certain theoretical as well as practical implications. The market participants in equity market can improve the forecasting of liquidity of their investment portfolio by employing monetary policy along with individual asset's characteristics. Regulators and policymakers may consider the cross-sectional relationship between stock liquidity and monetary policy as an important source of information for policy formulation and implementation. JEL Classification: E44, E51, G12